Nationwide analysis of hospital variation in preoperative radiotherapy use for rectal cancer following guideline revision. Issue 3 (March 2020) - Detering, Robin; de Neree tot Babberich, Michael P.M.; Bos, Amanda C.R.K.; Dekker, Jan Willem T.; Wouters, Michel W.J.M.; Bemelman, Willem A.; Beets-Tan, Regina G.H.; Marijnen, Corrie A.M.; Hompes, Roel; Tanis, Pieter J.
Abstract: Introduction: The revised Dutch colorectal cancer guideline (2014), led to an overall decrease in preoperative radiotherapy (RT) use. This study evaluates hospital variation in RT use for resectable rectal cancer and the influence of guideline revision, including the nationwide impact of changing RT application on short term outcomes. Methods: Data of surgically resected rectal cancer patients registered in the Dutch ColoRectal Audit were extracted between 2011 and 2017. Patients were divided into groups based on time of guideline revision (<2014 and ≥ 2014). Primary outcome was guideline adherence at hospital level regarding RT application, stratified for three stage groups. Secondary outcomes included positive circumferential resection (CRM+) and 30-day complicated postoperative course. Results: The groups consisted of 7364 and 12, 057 patients, respectively. In total, 6772 patients did not receive RT (17.6% (<2014) vs. 45.7% (≥2014), p < 0.001). The largest increase of surgery alone was observed for cT1-2N0 stage rectal cancer (35.1% vs. 91.8%, p < 0.001), with a substantial decrease in hospital variation (IQR 22.2–50.0% vs. IQR 87.6–98.0%). For cT1-3N1MRF- stage rectal cancer, a substantial amount of hospital variation in short course RT remained after guideline revision (IQR 26.8–54.1% vs. IQR 26.2–50.0%). A significant decrease in CRM+ (5.8% vs. 4.2%, p < 0.001) and complicated course (22.5% vs. 18.5%, p < 0.001) was observed. Conclusions: Radiotherapy for early-stage rectal cancer was uniformly abandoned after guideline revision, while substantial hospital variation remained for intermediate risk resectable rectal cancer in the Netherlands. The substantial nationwide decrease in the use of RT for rectal cancer treatment did not negatively impact CRM involvement.